Weight-related differences in salience, default mode, and executive function network connectivity in adolescents - Borowitz, Michelle A. (Obesity (Silver Spring), 2020)
OBJECTIVE: The current study examined whether adolescents with weight ranging from lean to obese showed weight-related differences in the default mode network (DMN), executive function network (EFN) and the salience network (SN). METHODS: One-hundred sixty-four adolescents participated in a resting-state functional connectivity (rsFC) scan. A general linear model (GLM) was used to examine differences in rsFC patterns between adolescents with lean weight, overweight, and obesity. RESULTS: Adolescents with obesity compared to those with lean weight showed stronger within-SN connectivity between the medial orbitofrontal cortex (OFC), olfactory tubercle, and pallidum, however showed lower connectivity between the amygdala and SN regions (nucleus accumbens, thalamus, putamen). Those with obesity also showed lower connectivity between SN (amygdala, caudate) and DMN (parahippocampus, hippocampus, precuneus) regions. Adolescents with obesity compared to those with lean weight showed lower connectivity between SN (medial OFC) and EFN (ventrolateral prefrontal cortex) regions. CONCLUSIONS: Obesity appears to be related to stronger connectivity within and between regions implicated in determining salience of stimuli, which may have implications for reward processing. Lower connectivity between SN and EFN regions may suggest that executive control efforts are going “offline” when salience and reward processing regions are engaged in adolescents who are obese.